2018
DOI: 10.1038/s41598-018-35364-w
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Stretching Reduces Tumor Growth in a Mouse Breast Cancer Model

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nine studies explored the effect of stretching employing different longer-term stretching protocols [ 8 , 25 28 , 40 , 42 , 43 , 47 ]. These studies performed the inflammatory assessment at the end of the stretching intervention, or 12- to 24-hours post-intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies explored the effect of stretching employing different longer-term stretching protocols [ 8 , 25 28 , 40 , 42 , 43 , 47 ]. These studies performed the inflammatory assessment at the end of the stretching intervention, or 12- to 24-hours post-intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, circulating tumor cells were killed at high shear forces via an oxidative stress-induced mitochondrial apoptotic pathway ( Regmi et al, 2017 ). Further, it was reported that exercise or mechanical stretching of tumors caused tumor regression in a mouse model ( Betof et al, 2015 ; Berrueta et al, 2018 ). All these studies indicated that mechanical stresses could inhibit cancer growth.…”
Section: Introductionmentioning
confidence: 99%